OsMORF9 is necessary for chloroplast development and seedling survival in rice. (June 2021) - Zhang, Qiang; Wang, Yaliang; Xie, Wei; Chen, Changzhao; Ren, Deyong; Hu, Jiang; Zhu, Li; Zhang, Guangheng; Gao, Zhenyu; Guo, Longbiao; Zeng, Dali; Shen, Lan; et al.
Highlights: OsMORF9 is highly expressed levels in leaves and localized in chloroplasts. OsMORF9 affects chloroplast gene editing and splicing processes in rice. OsMORF9 interacts with OsSLA4 and DUA1. Abstract: Chloroplasts are closely associated with the growth and development of higher plants. Accumulating evidence has revealed that the multiple organellar RNA editing factors (MORF) family of proteins influences plastidic and mitochondrial development through post-transcriptional regulation. However, the role of MORFs in regulating the development of chloroplasts in rice is still unclear. The OsMORF9 gene belongs to a small family of 7 genes in rice and is highly expressed in young leaves. We used the CRISPR/Cas9 system to mutate OsMORF9 . The resulting knockout lines osmorf9−1 and osmorf9−2 exhibited an albino seedling lethal phenotype. Besides, the expression of many plastid-encoded genes involved in photosynthesis, the biogenesis of plastidic ribosomes and the editing and splicing of specific plastidic RNA molecules were severely affected in these two OsMORF9 mutants. Furthermore, yeast two-hybrid analysis revealed that OsMORF9 could interact with OsSLA4 and DUA1 which are members of the pentatricopeptide repeat (PPR) family of proteins. Analysis of subcellular localization of OsMORF9 also suggested that it might function in chloroplasts. The findings from the present study demonstrated the critical role of OsMORF9 in the biogenesis of chloroplast ribosomes, chloroplast development and seedling survival. This therefore provides new insights on the function of MORF proteins in rice.